The Dry River Diorite: Insights into mantle contributions to the younger White Mountain Magma Series, New Hampshire, USA - Dorais, Michael J.; Kinney, Sean T.; Apen, Francisco E.; Niespolo, Elizabeth M. (Atlantic Geoscience, 2025)
The Dry River Diorite is one of the few mafic bodies spatially associated with the White Mountain Batholith of New Hampshire, USA. However, new U–Pb zircon geochronology reveals a 119.92 ± 0.62 Ma emplacement age for the diorite, considerably younger than the ca. 200–180 Ma batholith and indicates that it is instead a member of the younger White Mountain Magma Series (ca. 130–100 Ma) of the New England–Quebec province. The diorite is mildly silica undersaturated, with chondrite-normalized REE and spider diagram patterns that indicate ocean island basalt compositions. Several tectonic discrimination diagrams indicate the magmas have within-plate basaltic compositions. Ce/Yb versus La/Ta and Sm/Yb versus La/Sm values indicate the magmas are 2–5% partial melts of garnet peridotites. ƐNd and initial 87Sr/86Sr values range between 4.27 to 3.44 and 0.7036 to 0.7040 respectively. All these geochemical characteristics are identical to those of the mafic rocks of eastern Monteregian Hills and the Ossipee complex basalts of central New Hampshire. Modeling of the Dry River Diorite as the mafic endmember of the felsic rocks of the younger White Mountain Magma Series indicates that the felsic rocks contain up to 50% crustal endmember.Previous high-precision geochronological studies indicated a relatively brief period of magmatism across this region and have argued that observed age progressions of continental magmatism are consistent with the Great Meteor Hotspot hypothesis for their formation. The age produce here for the Dry River Diorite is consistent with this trend’ however, the younger-than-predicted age is likely the result of Pb-loss or complex geological factors. Although the Cretaceous magmatic rocks in this region do not easily fit a linear age progression as a simple hotspot model might predict, the confluence of geodynamic processes that have shaped this region over 200 myr are not simple and require a high standard of verification for any one hypothesis. Whether these magmas resulted from complex hotspot dynamics, asthenospheric upwelling, or some other mechanism or combination of mechanisms requires a clear path to deconvolve the role each process had in shaping the magmatic history we can now observe. The new geochronologic data we present is consistent with other ca. 120 Ma, geographically proximal plutons in the region and therefore consistent with the age progression a hot spot model would predict for a large fraction of the Cretaceous magmatism observed across the region; however this does not preclude other models, e.g., edge-driven convection, for parsimoniously explaining magmatism in the region that does not conform to this track.